Influência da vazão de injeção sobre a uniformização do perfil de fluxo em poços horizontais - Silva Mantegazini, Isabela; Romero, Oldrich Joel (Latin American Journal of Energy Research, 2022)
Non-uniform flux profiles caused by the pressure loss in horizontal wells decreases the injectivity and the sweep efficiency. Several techniques for flow profile equalization were developed, due to companies concern to increase the final recovery, and among them is the divergent perforation, that consists in the differentiated distribution of the holes on the completion liner. This study aimed to illustrate how the described technique works and to determine the influence of the injection flow rate on the pressure loss and, thus, on the flux profile in horizontal wells. It was concluded that the flux profile follows the pressure loss behavior and that the cases with higher injection flow rate resulted in greater profile equalization.